Activation of Baculovirus Very Late Promoters by Interaction with Very Late Factor 1 - Yang, Song (American Society for Microbiology, 1999)
Very late factor 1 (VLF-1) of Autographa californica multicapsid nuclear polyhedrosis virus (AcMNPV) activates the transcription of two genes, polyhedrin (polh) and p10, during the final, occlusion-specific phase of infection. Using transient expression assays responsive to VLF-1, we identified linker scan mutations in the polh and p10 promoters which abolished or weakened the ability of the promoters to respond to stimulation by VLF-1. These mutations were located between the transcriptional and translational initiation sites, a region previously shown to be essential for the burst of expression during the very late phase. Addition of partially purified, epitope-tagged VLF-1 to DNA encompassing this “burst sequence” resulted in a shift in the gel electrophoretic mobility of the DNA, indicating that VLF-1 forms a complex with DNA. Addition of an antibody specific for the epitope tag of VLF-1 decreased the mobility of the DNA further, confirming the presence of VLF-1 in the complex. DNase I footprint assays revealed that VLF-1 partially purified from either insect cells or bacterial cells interacted with the burst sequences of both the polh and p10 very-late promoters. Linker scan mutations within the burst sequences severely impaired interaction between VLF-1 and the promoters. We propose that VLF-1 transactivates the polh and p10 promoters by interacting with the burst sequences.